SYNTHESIS OF SECONDARY ALCOHOL COMPOUNDS FROM SAFROLE AND METHYLEUGENOL - Hanoch J Sohilait; Hardjono Sastrohamidjojo; Sabirin Matsjeh (Universitas Gadjah Mada, 2003)
Synthesis of secondary alcohols compound from safrole and methyleugenol has been achieved through conversion of allyl group to alcohol.The reaction of safrole and methyleugenol with mercuric acetate in aqueous tetrahydrofuran, followed by in situ reduction of the mercurial intermediate by alkaline sodium borohydride produced secondary alcohol namely safryl alcohol (71.25%) and methyleugenil alcohol (65.56%). The structure elucidation of these products were analyzed by FTIR, 1H-NMR, 13C-NMR and MS.